Factors affecting the financial performance of mining companies in South Africa - Khorombi, Mpho (My University, 2017)
The South African economy is built on the richness of mineral resources found in most parts of the country. In 2013, Chamber of Mines reported that the country earned about R 2.4 trillion from the export market over the past 10 years. However, the industry has also shown signs of financial ill health in recent years. This study examines the factors affecting the financial performance (return on capital invested, return on asset and stock price return) of mining companies in South Africa with a particular focus on employee related factors (number of employees, wage bill and safest statistics). The study examines 24 publicly listed companies over a 6 year period using panel data analysis. The results show that lost time injury rate, number of fatalities are significant variables in explaining the changes in financial performance. Labour indicators such as number of employees, lost time injury rate and wages have a negative relationship with all financial indicators.
Thesis (M.M. (Finance & Investment)--University of the Witwatersrand, Faculty of Commerce, Law and Management, Wits Business School, 2017
Keywords: Mineral industries--South Africa--Economic aspects; Stocks--Prices--South Africa